In praise of meat, milk and eggs - Cherfas, Jeremy (Eat This Podcast, 2017)
Excluding animal products from your diet as a vegetarian or vegan is a choice some people have the luxury to make, and if they know what they’re doing, and take care, they can be perfectly healthy. But there are probably far more people who have no choice in the matter. They would eat meat if they could, but they simply can’t afford it. For those people, a little bit of animal source food – milk, meat, eggs – can make a great difference to their health and wellbeing. It can be easy to forget that, in the clamour for meatless Mondays and other efforts to respond to climate change. There’s also the fact that in many parts of the world, animals play a very useful role in transforming things people can’t or won’t eat, like grass, into good food.